Práticas de consciência fonológica: brincar alfabetizando no último ano da educação infantil e alfabetizar letrando no primeiro ano do ensino fundamental - Pena, Nathália Nepomuceno (Universidade Federal de São Carlos, 2020)
This monograph has the general objective of understanding how the domain of phonological awareness practices contributes to literacy and literacies from the theoretical foundations and reflections on the practices of Soares (2017) and Morais (2019). It is a bibliographic and documentary research that seeks to problematize some concepts directly and indirectly related to phonological awareness and to analyze, in a perspective of playing literacy and literacy literacy, practices in teachers' reports and games in the transition between the last year of Early Childhood Education and the first year of elementary school. Regarding the concept of phonological awareness, it was possible to observe that, according to Morais (2019), this concept should not be seen in the singular, but as a “constellation of skills” that involves, according to Soares (2017), lexical awareness, syllabic awareness, awareness of rhymes and alliterations and phonemic awareness. Regarding the reports and games, it was possible to show that the teacher plays a central role both in the planning of situations, with the use of games to help in the process of literacy and literacy of children, and in the monitoring of students during their realization. In this sense, the research enables us to understand the importance of building, as literacy teachers, a pedagogical work in which we and children can build moments of playing with words and reflecting on their sound parts.
Phonological awareness practices: playing literacy in the last year of early childhood education and literacy by writing in the first year of elementary school
Keywords: Consciência fonológica; Brincar alfabetizando; Alfabetizar brincando; Educação Infantil; Ensino Fundamental; Phonological awareness; Playing literacy; Literacy while playing; Child education; Elementary School; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM